Business lending - Lyons, Peter; Institute of Financial Services (Great Britain) (Kent, U.K. : Institute of Financial Services, 2005)
The book examines issues relevant to: the management of a bank's lending portfolio and lending strategy; the assessment of the credit worthiness of business customers; the evaluation of lending propositions; lending control and recovery and the nature of specialist services relevant to business lending.
Includes index.
nmn 17/05/13
Loans
Keywords: Commercial lending; Business lending